Spiral-curricular blended learning for the mathematical methods in physics education—A cross-modular interactive course - Kämpf, Lydia; Bauer, Jan; Stallmach, Frank (Frontiers in Education, 2025)
A research based concept for the mathematics education of physics teacher trainees is introduced, which integrates mathematical methods seminars in the experimental physics courses of the first two semesters. This article reports on the implementation and evaluation of a spiral-curricular blended learning approach for the mathematical methods seminars, which is based on design criteria for digital teaching-learning sequences. Evaluations of the course quality show a high level of student satisfaction with the materials, especially with the interactive videos. The interactivity was found to be a central criterion for the quality of the explanatory videos. Surveys on the learning progress for the topics complex numbers and differential equations revealed good to very good test results. Detailed investigations on paired samples showed that knowledge was consolidated, resulting in a trend to a narrower and higher test score distributions with ongoing duration of the course.